Microsurgical Breast Reconstruction in Patients with Disorders of Hemostasis: Perioperative Risks and Management. (28th September 2022) - Speck, Nicole E.; Hellstern, Peter; Farhadi, Jian
Abstract : Background: Surgical and technological advances have resulted in the widespread adoption of microsurgical breast reconstruction. Many comorbidities that potentially might impair vasculature and wound healing are no longer considered contraindications for these procedures. However, some uncertainty still prevails regarding the perioperative management of patients with disorders of hemostasis. Methods: The authors combined a literature review with a retrospective chart review of patients with disorders of hemostasis who had undergone microsurgical breast reconstruction at the senior author's (J.F.) center between 2015 to 2020. Several disorders associated with thrombotic and/or hemorrhagic complications were identified, and a standardized risk assessment and management strategy was developed in cooperation with a hematologist. Results: Overall, 10 studies were identified comprising 29 patients who had a defined disorder of hemostasis and underwent microsurgical breast reconstruction. Seventeen microsurgical breast reconstructions were performed on 11 patients at the senior author's (J.F.) center. High factor VIII levels, heterozygous factor V Leiden, and heterozygous prothrombin mutation G20210A were the most common genetic or mixed genetic/acquired thrombophilic conditions. As expected, hereditary antithrombin, protein C, or protein S deficiencies were rare. Among hemorrhagic disorders, thrombocytopenia, platelet dysfunction, and von Willebrand disease or low von Willebrand factor levels were those factors most frequently associated with increased perioperative bleeding. Conclusions: Patients should be screened for elevated risk of thrombosis or bleeding before undergoing microsurgical breast reconstruction, and positive screening should prompt a complete hematologic evaluation. Interdisciplinary management of these disorders with a hematologist is essential to minimize risks and to obtain optimal reconstructive results. CLINICAL QUESTION/LEVEL OF EVIDENCE: Risk, IV.